Identificação de um grupo de competências individuais segundo a percepção de gestores e líderes em empresa de médio porte do ramo eletro-eletrônico: um estudo de caso - (:unkn) unknown (Universidade Federal do Amazonas, 2005)
Based on concepts of competences, this research paper aims mainly to identify, according to the perception of administrators and leaders, which relevant individual competences for searching the growth of the organization and the professional will have to be considered by the electrical and electronic goods sector of the Industrial Pole of Manaus, especially in mid-sized companies. It was also tried to confront the differences of perception among the analyzed groups concerning the competences. The research was oriented by focusing on the approach to the competences and individuals inside the organizations, especially by Philippe Zarifian and Guy Le Boterf, and also by adding contributions of several other authors. The research had this descriptive, exploratory and applied character. The data for the study were collected through a structured questionnaire, not disguised, and helped measure the degree of importance of forty-nine relevant competences classified in five dimensions. A census has been made, which was constituted by thirty managers and leaders. The descriptive analysis and the comparative analysis of the averages among the competences, dimensions and groups studied have been done. It has been verified that the average of the degrees of importance attributed by the managers and supervisors is significantly higher than the sample averages of leaders. Besides, the degree of perception of each dimension of the competence also presents significant differences. The study indicates the necessity not only to adjust the difference of perception that the different hierarchical levels have concerning the same individual competences, but also to balance the importance noticed by the group in relation to each dimension, with the aim of obtaining a good professional performance. At the end of the paper, recommendations are made in order to do new research on academic and organizational areas. The result of this research will serve as source of information to the administrators of companies located in the Industrial Pole of Manaus for analyses, considerations and comparisons with their own organizations.
Keywords: Competências individuais; Gestão por competência; Comportamento organizacional; Perfil do Gestor; Vantagem Competitiva; Engenharia de produção.; Individual competences; Management by Competence; Organizational behavior; Administrator s profile; Competitive Advantage; Production Engineering; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO